Uncontrolled recurrent myasthenia gravis exacerbations secondary to chronic gabapentin use. Issue 4 (4th July 2019) - Chien, Jason L.; Baez, Valentina; Mody, Harshad R.
ABSTRACT: Gabapentin is an anticonvulsant medication that reduces synaptic transmission by decreasing presynaptic voltage-gated Ca2+ and Na+ channels. It is approved to treat focal seizures but also used to treat post-herpetic and neuropathic pain. Although uncommon, there have been three reported cases of myasthenia gravis exacerbation associated with gabapentin in the literature. We present a patient with uncontrolled recurrent myasthenia gravis exacerbations secondary to chronic gabapentin use and provide a review for the three published cases.